PENGARUH PENERAPAN STRATEGI ACTIVE LEARNING TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 2 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Husaipah, Husaipah; Nursyahra, Nursyahra; Megahati, RRP. (Pendidikan Biologi, 2014)
ABSTRAKÂ There are several factors which influence the low-mark of students, in Biology subject such as low-interested of student, felt borning while learning and pasive in learning process which mean that students tend te beâun brave to express their opinion so it is difficult to know how far students understanding about the material. At least, teacher become the center of learning.One way to solve this problem is by giving active learning strategy type Giving Question and Getting Answer toward students Biologi achievement class VII SMPN 2 Ranah Batahan Kabupaten West Pasaman. The type of this reseach is experimental with Randomized Control- Group Posttest only design. Population of this research is second semester of students class VII SMPN 2 Ranah Batahan academic year 2013/2014. Which Consist of three classes. Purposive Sampling is used in technique of sampling which is gotten Â as experimental class and Â as control class. Test is used as final instrument in objektif form which consist of 28 items. Data analysis is done by t-test with criterion t-calculate > t-table. From the data analysis it can be gotten, the average of students Biologi mark in experimental class 76,78 with 10,32 standard deviation , otherwise, control class with 58,13 in average and 12,56 standard deviation. From t-test analysis, it can be proven t- calculate (5,79) >t-table (1,68). It can be concluded that, Active Learning Strategy type Giving Question and Getting Answer can improve students Biologi achievement class VII SMPN 2 Ranah Batahan